2015
DOI: 10.1590/s1806-92902015000100005
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and blood parameters of bulls fed diets containing babassu mesocarp bran and whole or ground corn

Abstract: -The objective of the present study was to evaluate the effects of corn milling and the inclusion of babassu mesocarp bran (BMB) on productive performance, digestibility of dietary nutrients, and blood parameters of dairy crossbred (Holstein-Gyr) bulls finished in confinement. Twenty-four bulls were fed four different experimental diets, containing two levels of inclusion of BMB (0 and 41.24%) and corn supplied in two different forms (ground and whole), for 98 days (77 days of data collection and 21 days of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
2
4
0
Order By: Relevance
“…The similar feed conversion between BMB levels can be attributed, mainly, to the similar animal performance. These results were consistent with some reported in the literature (Silva et al, 2012;Cruz et al, 2014;Santana et al, 2015), which have demonstrated that when BMB inclusion levels are low to moderate, the lack of change in animal performance usually results in similar feed conversion, even when DM intake is changed. However, when the BMB inclusion levels reduced animal performance, which occurred for higher levels of BMB inclusion in this study, feed conversion increased (Miotto et al, 2013;Alencar et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The similar feed conversion between BMB levels can be attributed, mainly, to the similar animal performance. These results were consistent with some reported in the literature (Silva et al, 2012;Cruz et al, 2014;Santana et al, 2015), which have demonstrated that when BMB inclusion levels are low to moderate, the lack of change in animal performance usually results in similar feed conversion, even when DM intake is changed. However, when the BMB inclusion levels reduced animal performance, which occurred for higher levels of BMB inclusion in this study, feed conversion increased (Miotto et al, 2013;Alencar et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The higher NDF intake with BMB inclusion in the diet can be attributed to the high fiber content of the feed, which was consistent with results reported in the literature (Miotto et al, 2013;Cruz et al, 2014;Santana et al, 2015). However, the literature shows that, in general, an increase in the proportion of sugarcane in cattle diets reduces NDF intake due to the decrease in DM intake (Magalhães et al, 2004(Magalhães et al, , 2006.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations